M.K. Ranjitsinh & Ors. v. Union of India & Ors, analysed through the lens of climate change and governance - Baskar, Siddharth; Malaviya, Deepayan (International journal of economic perspectives, 2026)
The activities of humans have resulted in the deterioration of the climate, which is having obvious and severe repercussions—not only for humans but also for other species. The unprecedented rainfall and flooding that took place in 2024 led to a significant number of people to lose their lives across a number of countries. This was a direct result of the increase of temperature and other environmental events that took place during that year. People were also confronted with a great deal of economic difficulties. As a consequence of these impacts, a significant number of animal species are currently in jeopardy of becoming extinct. The sustainability of humans and other species is being gravely endangered by climate change and over the course of the past few years, the adverse effects of climate change have made the conditions for an extensive number of species extremely challenging. Within the framework of this investigation, the subject of biodiversity conservation and the part that the Hon’ble Supreme Court played in the safeguarding of the Great Indian Bustard will be investigated in greater depth. Furthermore, the Hon’ble Court, in this particular case, advocated for the observance of sustainable development goals and the escape from the effects of climate change. It is a fact that climate change is a real phenomenon.